1988
DOI: 10.1128/mcb.8.6.2367
|View full text |Cite
|
Sign up to set email alerts
|

Putative genes of a variant-specific antigen gene transcription unit in Trypanosoma brucei.

Abstract: In a 7-kilobase (kb) sequence upstream from the 5' barren region, the Trypanosoma brucei AnTat 1.3A expression site carries two putative genes, named ESAG 2 and ESAG 3 for expression site-associated genes, as well as a copy of ESAG 1 (D.F. Cully, H.S. Ip, and G.A.M. Cross, Cell 42:173-182, 1985). At least 3 kb of this expression site exhibits a high degree of homology with the silent telomere carrying the AnTat 1.3A basic copy, whose ESAG 1 is interrupted by stop codons. Like the antigen gene, the region conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…In accordance with the data from Northern blots, the results showed that GRESAG 2.1 and ESAG 2 primarily hybridized with transcripts from procyclic and bloodstream nuclei, respectively. Transcription of GRESAG 2.1 appeared to be fully resistant to 1 mg of a-amanitin per ml, while that of ESAG 2 appeared to be relatively sensitive (panel 1, lanes B and B + am), as reported previously (1,27).…”
Section: Methodssupporting
confidence: 48%
See 3 more Smart Citations
“…In accordance with the data from Northern blots, the results showed that GRESAG 2.1 and ESAG 2 primarily hybridized with transcripts from procyclic and bloodstream nuclei, respectively. Transcription of GRESAG 2.1 appeared to be fully resistant to 1 mg of a-amanitin per ml, while that of ESAG 2 appeared to be relatively sensitive (panel 1, lanes B and B + am), as reported previously (1,27).…”
Section: Methodssupporting
confidence: 48%
“…UV irradiation was performed under the conditions defined by Johnson et al (13 (1,27). In procyclic forms, the early data suggested only ot-amanitin-sensitive transcription of ESAG 2-related sequences (27), but it was subsequently found that this transcription also included a-amanitin-resistant components (24 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures for DNA and RNA isolation, Southern and Northern (RNA) blot 1ybridization, as well as DNA cloning, were as described (1,18). cDNA libraries were constructed in lambda gtlO according to Gubler and Hoffman (6) homologous sequences from other telomeres show differences ( Fig.…”
Section: Methodsmentioning
confidence: 99%